Untangle your emotions : naming what you feel and knowing what to do about it - Allen, Jennie (WaterBrook, 2024)
"The New York Times bestselling author of Get Out of Your Head provides a revolutionary path to embracing a healthy relationship with your emotions, one that leads to life-giving connection with God and others as well as to a richer understanding of yourself"--